UPAYA MENINGKATKAN PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MAGELANG - Susilo, Susilo; Sutrischastini, Ary; Linawati, Linawati; Gusti, Yenny Kurnia (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
The objectives of this research are 1) to identify the causes of not yet optimal public services at the Magelang City Population and Civil Registration Service, 2) to formulate efforts to improve public services at the Magelang City Population and Civil Registration Service. This research is qualitative research. Data collection techniques were carried out using interviews. The research informants were 3 people consisting of 1 functional official in the Civil Registration Services Sector, 1 service officer and 1 community member who received services from the Magelang City Population and Civil Registration Service. Data analysis consists of three flows, namely data reduction, data presentation and drawing conclusions.The results of the research show that 1) The reasons why the services of the Magelang City Population and Civil Registration Service are still not optimal are: a. low competency of officers so that service becomes less fast; b. lack of facilities for population document services and civil registration; c. innovation in population services and civil registration is not yet optimal; d. There are still people who do not know about the various population and civil registration services. 2) Efforts to improve public services at the Magelang City Population and Civil Registration Service are as follows: a. improve technical and functional training in population administration organized by Ministries/L/Provincials or Universities to improve population services and civil registration, b. apply for budget assistance from the central government in order to improve population document and civil registration service facilities, c. increase ASN with functional computer officer positions to support innovation in population and civil registration services, d. increase socialization to the public regarding information on various population services and civil registration.